The Role Of Government Public Relations In Efforts To Prevent Early-Age Marriages - Hendrarso, Panji; Mayagita, Avradya; Poernomo, Baby (International Journal of Educational Research & Social Sciences, 2023)
Child marriages are still common in Indonesia. In reality, early age marriage will have a negative impact on the perpetrators and this will affect their personal and social life, so that if this is not anticipated it will be miserable for the perpetrators, who are children who are still early age. Therefore the role of government Public Relations is very demanding. This is a descriptive qualitative research. Data collection was carried out using semi-structured interviews with 9 informants consisting of 3 women who were married under the age of 18, 4 teachers and 2 public relations staff of government institutions. This research shows that the operational strategy, persuasive and educative approach, responsibility approach and collaborative approach related to the underage marriage prevention program must be properly implemented in order to carry out the duties and functions of Public Relations in government institutions, so that the program's main objectives can be achieved.